Enhanced resistance to Cryptococcus neoformans infection induced by chloroquine in a murine model of meningoencephalitis. - Mazzolla, R (1997)
Although the pathogenesis of cerebral cryptococcosis is poorly understood, local immune cells, such as microglia and astrocytes, likely play a critical role in containing infection. Chloroquine (CQ) is a weak base that accumulates within acidic vacuoles and increases their pH. Consequently, proteolytic activity of lysosomal enzymes and intracellular iron release/availability are impaired, resulting in decreased availability of nutrients crucial to microorganism survival and growth in the host. We found that CQ enhances BV2 microglial-cell-mediated anticryptococcal activity in vitro. The phenomenon is (i) evident when both unopsonized and opsonized microorganisms are used and (ii) mimicked by NH4Cl, another weak base, and by bafilomycin A1, an inhibitor of vacuolar-type H+-ATPases. In vivo, intracerebral administration of CQ before lethal local challenge with Cryptococcus neoformans results in a significant augmentation of median survival time and a marked reduction of yeast growth in the brain and is associated with the enhancement of local interleukin 1beta (IL-1beta) and IL-6 mRNA transcripts. Overall, these results provide the first evidence that CQ enhances anticryptococcal host defenses.